Patient perspectives on treatment decision-making under clinical uncertainty: chemotherapy treatment decisions among stage II colon cancer patients. Issue 10 (27th May 2021) - Brotzman, Laura E; Crookes, Danielle M; Austin, Jessica D; Neugut, Alfred I; Shelton, Rachel C
Abstract: The decision to use adjuvant chemotherapy (ACT) after surgical resection for stage II colon cancer remains an area of clinical uncertainty. Many patients diagnosed with stage II colon cancer receive ACT, despite inconclusive evidence of long-term clinical benefit. This study investigates patient experiences and perceptions of treatment decision-making and shared decision making (SDM) for ACT among patients diagnosed with stage II colon cancer. Stage II colon cancer patients engaged in treatment or follow-up care aged >18 years were recruited from two large NYC health systems. Patients participated in 30–60-min semi-structured interviews. All interviews were transcribed, translated, coded, and analyzed using a thematic analysis approach. We interviewed 31 patients, of which 42% received ACT. Overall, patient perspectives indicate provider inconsistency in communicating ACT harms, benefits, and uncertainties, and poor elicitation of patient preferences and values. Patients reported varying perceptions and understanding of personal risk and clinical benefits of ACT. For many patients, receiving a clear treatment recommendation from the provider limited their participation in the decision-making process, whether it aligned with their decisional support preferences or not. Findings advance understanding of perceived roles and preferences of patients in SDM processes for cancer treatment under heightened clinical uncertainty, and indicate a notable gap in understanding for decisions made using SDM models in the context of clinical uncertainty. Educational and communication strategies and training are needed to support providers in communicating uncertainty, risk, treatment options, and implementing clinical guidelines to support patient awareness and informed decisions. Abstract : Patients with stage II colon cancer weigh provider recommendations, the balance of risks and benefits, and their personal preferences when making decisions about chemotherapy treatment.